Pulmonary Complications of Cystic Fibrosis - Garcia, Bryan; Flume, Patrick A. (Seminars in Respiratory and Critical Care Medicine, 2019)
Cystic fibrosis (CF) lung disease is characterized by the development of progressive bronchiectasis and impaired lung function with severe airflow obstruction. CF patients suffer from shortened life expectancy, primarily driven by respiratory failure. The mechanism by which CF lung disease develops is the result of an interplay of multiple intrinsic and extrinsic factors including genotype, abnormalities in mucus composition and movement, chronic inflammation, and chronic airway infection. Although all CF patients are at increased risk for pulmonary complications including hemoptysis, pneumothorax, pulmonary hypertension, and chronic hypoxic and hypercapnic respiratory failure, the risk of developing these complications increases with progression of lung disease. The focus of this article is to summarize the pathophysiology, epidemiology, and management of these key pulmonary complications.
Keywords: cystic fibrosis; complications; hemoptysis; pneumothorax; pulmonary hypertension; respiratory failure